Struktur Kebahasaan Bahasa Indonesia sebagai Rujukan Penggunaan Bahasa (Fonologi) - Nur Santy; Rahma Ashari Hamzah; Nurul Arista (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The Indonesian language functions as the main communication tool as well as a symbol of national identity in the social and cultural life of the community. In the midst of the diversity of more than 700 regional languages, the importance of using the Indonesian language properly and correctly becomes very crucial to support communication between regions. One of the important elements in the use of language is phonology, which is a branch of linguistics that discusses the sounds of language and their function in distinguishing meanings. Understanding of phonology is very influential in the language learning process, because errors in pronunciation can cause a shift in meaning. In the context of globalization and the rampant influence of foreign languages, understanding phonology also helps preserve the authenticity of the Indonesian language without losing its linguistic identity. Therefore, learning phonology should be used as an important part of the Indonesian curriculum in schools, in order to hone students' language skills and raise awareness of the importance of maintaining language preservation from an early.